Implementasi Pengaman Pintu Terintegrasi dengan Kartu Anggota pada Ruangan Sekretariat Himpunan Mahasiswa Teknik Elektro Universitas Pamulang - Fadhlan Ibnur Khoir (Jurnal Publikasi Teknik Informatika, 2025)
The electronic lock using RFID facilitates access in and out and provides more security compared to conventional door locks. Pamulang University Electrical Engineering Student Association (HIMA) has a door lock system in the HIMA secretariat room using a manual key and does not yet have a member card for their members. For this reason, the HIMA member card with RFID-based door security is expected to facilitate access and increase security in the HIMA secretariat room. The variables in this study are HIMA member cards, access time response on the system, hardware reliability on the system, and electrical voltage on hardware components. Based on the research results, it can be concluded that the door security system can be implemented by showing that the hardware components in the system work well and can receive input and output according to their working principles. The average card reading response speed is around 7.73 seconds using a HIMA member card and 7.29 seconds using an unregistered card. The type of card that can open the door to the HIMA secretariat room can only 10 HIMA member card, apart from this card the door remains locked. The measured electrical voltage on the NodeMCU ESP8266 device components was 4.94VDC, the Door Lock Solenoid was 12.07VDC, the LCD was 4.05VDC, the Buzzer was 1.41VDC, the RFID Reader MFRC522 was 2.78VDC, and the Relay was 4.96VDC. The database system can be recorded on Google Spreadsheet by displaying the results of entry access using HIMA member cards and unregistered cards and can be monitored in real time or as a database for entry access to the HIMA secretariat room.